Conservation status of Italian coastal dune habitats in the light of the 4th Monitoring Report (92/43/EEC Habitats Directive) - Prisco, Irene; Angiolini, Claudia; Assini, Silvia; Buffa, Gabriella; Gigante, Daniela; Marcenò, Corrado; Sciandrello, Saverio; Villani, Mariacristina; Acosta, Alicia T.R. (Plant sociology, 2020)
Coastal dunes are among habitats with the worst conservation status on a global, European and national scale. Monitoring and reporting are of strategic importance to determine the effectiveness of the implementation of Habitats Directive and to preserve the unique biodiversity heritage of the Italian dunes. In this study we show main results of the 4th National Report with specific reference to the macro-habitat “Coastal Sand Dunes and Inland Dunes”, highlighting its updated current conservation status at the national and Biogeographical level. A comprehensive Working Group of territorial experts collected, updated, validated and integrated the data available for 11 Annex I Habitats, distributed in the Alpine, Continental and Mediterranean Biogeographical Regions. The conservation status was evaluated through the following criteria: geographic range, surface area, structure, functions, pressures, threats, conservation measures and prospects. Results highlighted the dramatically bad conservation status of Italian dune Habitats: the overall assessment reported 88% of habitats in bad conservation status and the remaining 12% is in inadequate conditions. Results showed a generalised threat and a worrying conservation status both on herbaceous and wooded communities, in particular in some relevant habitats, such as the shifting dunes. Main pressures and threats were linked to residential, commercial and industrial activities, as well as alien species. Although some of the changes in distribution and trends are probably deriving from more accurate and updated data, the alarming conservation status of Italian sand dunes requires a better knowledge of pressures and threats for further management actions and monitoring plans, inside and outside protected areas.